2013
DOI: 10.6004/jnccn.2013.0119
|View full text |Cite
|
Sign up to set email alerts
|

Adult Cancer Pain

Abstract: Pain is a common symptom associated with cancer and its treatment. Pain management is an important aspect of oncologic care, and unrelieved pain significantly comprises overall quality of life. These NCCN Guidelines list the principles of management and acknowledge the range of complex decisions faced in the management oncologic pain. In addition to pain assessment techniques, these guidelines provide principles of use, dosing, management of adverse effects, and safe handling procedures of pharmacologic therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(72 citation statements)
references
References 161 publications
1
70
0
1
Order By: Relevance
“…Characterizing recovery as the attainment of symptoms rated 0–3 on the 0–10 scale is based on the cutpoints used in multiple clinical practice guidelines, such as National Comprehensive Cancer Network fatigue and pain guidelines. 17,18 Empirical work has consistently demonstrated that substantial functional impairment occurs when symptoms reach moderate to severe levels. 19,20 Median and mean recovery days and 95% confidence limits (CL) were estimated using Kaplan–Meier analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Characterizing recovery as the attainment of symptoms rated 0–3 on the 0–10 scale is based on the cutpoints used in multiple clinical practice guidelines, such as National Comprehensive Cancer Network fatigue and pain guidelines. 17,18 Empirical work has consistently demonstrated that substantial functional impairment occurs when symptoms reach moderate to severe levels. 19,20 Median and mean recovery days and 95% confidence limits (CL) were estimated using Kaplan–Meier analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer is the leading cause of death worldwide, accounting for 7.6 million deaths (around 13% of all deaths) in 2008. Pain is a common and burdensome symptom associated with cancer and its treatment [1, 2]. Most of cancer patients suffered pain due to the cancer itself (the tumor pressed on bones, nerves, or other organs), the treatment, or the tests done to diagnose cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pain management is important in oncologic care and essential for maximizing patient outcomes [2, 4]. Mounting evidence showed that unrelieved pain significantly comprised overall quality of life and effective pain control was associated with survival [2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the NQF approach, criteria for selection of these outcomes included prevalence of the problems, known underdetection by providers despite substantial efforts, actionability, and appropriateness for patient self-reporting. Notably, clinical practice guidelines already exist in both of these areas, 10–12 with evidence that guideline adherence improves patient outcomes. 13,14 Both areas are well recognized as priorities by cancer care providers.…”
mentioning
confidence: 99%
“…The workgroup selected the National Cancer Institute’s PRO-CTCAE nausea items to serve as the assessment instrument. 10,11 These two items ask patients to rate their worst nausea severity and frequency of nausea during the last 7 days.…”
mentioning
confidence: 99%